If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -6(x + -4) = -1(6 + -1x) Reorder the terms: 5 + -6(-4 + x) = -1(6 + -1x) 5 + (-4 * -6 + x * -6) = -1(6 + -1x) 5 + (24 + -6x) = -1(6 + -1x) Combine like terms: 5 + 24 = 29 29 + -6x = -1(6 + -1x) 29 + -6x = (6 * -1 + -1x * -1) 29 + -6x = (-6 + 1x) Solving 29 + -6x = -6 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 29 + -6x + -1x = -6 + 1x + -1x Combine like terms: -6x + -1x = -7x 29 + -7x = -6 + 1x + -1x Combine like terms: 1x + -1x = 0 29 + -7x = -6 + 0 29 + -7x = -6 Add '-29' to each side of the equation. 29 + -29 + -7x = -6 + -29 Combine like terms: 29 + -29 = 0 0 + -7x = -6 + -29 -7x = -6 + -29 Combine like terms: -6 + -29 = -35 -7x = -35 Divide each side by '-7'. x = 5 Simplifying x = 5
| c/100=51/60 | | 7y-7-4y=4y-1 | | 8a-6=3a+29 | | 6/8=15/4 | | (4/x+3)^-1 | | -1/5=x+2/5 | | (4x/9)^-3 | | 0.1*4200(23-18)/0.435(92-23)= | | 1/2(2x+4)+4x=4(9x/2+3x/4) | | 5(3x-2)+1-3(2x+1)=2(x+1) | | 25x+17=192 | | 28x=8*42 | | 7x+7=4x+58/7 | | (29b-1)-7(4b+3)=-7 | | 54-6c= | | -9z-5=-95 | | 10x+38=188 | | 17+5x=19+x | | 2(x+2)=2x-9 | | 4/5+z=3/4 | | 11+4(3x-1)=5(2x+1)+2(2x-5) | | 49x^2-42x+2=0 | | 12x^2+x+5=8 | | 12-y=2y+3 | | 4y=-8x-8 | | 3x=-11 | | -4y-2x=4 | | f*6-5=1 | | 262-6x=39x+17 | | -4y-2y=4 | | 1+4(2x-6)-3(x+4)=0 | | 6x+13=85 |